Trends in the research design and application of mobile language learning: a review of 2007–2016 publications in selected SSCI journals. Issue 4 (19th May 2019) - Hwang, Gwo-Jen; Fu, Qing-Ke
ABSTRACT: This study reviewed the mobile technology-assisted language learning studies published from 2007 to 2016 in selected journals. Several critical issues were investigated, such as research methods, research issues, language and learner types, and learning outcomes. It was found that English as a foreign/second language was the most common target language; few studies have been conducted on native language learning. Early studies mainly focused on fostering learners' individual language skills, while in the recent 5 years, researchers started to consider the issue of delivering multiple language skills in authentic learning environments. In addition, an increasing number of studies have involved mixed methods and longer treatment periods. Moreover, the effectiveness of mobile learning in terms of speaking, writing, vocabulary, and pronunciation was generally identified by most of the studies. On the other hand, more evidence is needed to further confirm its impacts on listening, reading, grammar, and integrated/whole language learning. Finally, some suggestions are provided to researchers or practitioners to facilitate their future work.